PENGARUH PENERAPAN STANDAR AKUNTANSI PEMERINTAHAN, PEMANFAATAN TEKNOLOGI INFORMASI DAN KOMPETENSI SUMBER DAYA MANUSIA TERHADAP KUALITAS LAPORAN REALISASI ANGGARAN DENGAN SISTEM PENGENDALIAN INTERNAL SEBAGAI VARIABEL MODERASI - Sabrina, Mitsaal; Suwandi, Memen; Suhartono, Suhartono (ISAFIR: Islamic Accounting and Finance Review, 2024)
Abstract, This research aims to determine the effect of implementing government accounting standards, the use of information technology and human resource competence on the quality of budget realization reports with the internal control system as a moderating variable. This research is quantitative research with an associative descriptive approach. The data source was carried out by distributing questionnaires in 33 OPDs of Selayar Islands Regency with a total of 66 respondents. The results of research using multiple linear regression analysis show that partially the implementation of government accounting standards has an effect on the quality of budget realization reports, the use of information technology has no effect on the quality of budget realization reports, and human resource competence has an effect on the quality of budget realization reports. On the other hand, moderation regression analysis shows that the internal control system is unable to moderate the implementation of government accounting standards, the use of information technology, and human resource competence on the quality of budget realization reports Keywords: Implementation of government accounting standards, use of information technology, human resource competency, quality of budget realization reports, internal control system